Perspectives in dryland restoration: approaches for climate change adaptation - Ramón Vallejo, V.; Smanis, Athanasios; Chirino, Esteban; Ramo, V.; Fuentes, David; Valdecantos, Alejandro; Vilagrosa, Alberto (New Forests, 2012)
Reforestation efforts in dryland ecosystems frequently encounter drought and limited soil productivity, although both factors usually interact synergistically to worsen water stress for outplanted seedlings. Land degradation in drylands (e.g. desertiﬁcation) usually reduces soil productivity and, especially, soil water availability. In dry sub-humid regions, forest ﬁres constitute a major disturbance affecting ecosystem dynamics and reforestation planning. Climate change projections indicate an increase of drought and more severe ﬁre regime in many dryland regions of the world. In this context, the main target of plantation technology development is to overcome transplant shock and likely adverse periods, and in drylands this is mostly related to water limitations. In this paper, we discuss some selected steps that we consider critical for improving success in outplanting woody plants, both under current and projected climate change conditions including: (1) Plant species selection, (2) Improved nursery techniques, and (3) Improved planting techniques. The number of plant species used in reforestation is increasing rapidly, moving from a reduced set of well-known, easy-to-grow, widely used species, to a large variety of promising native species. Available technologies allow for reintroducing native plants and recovering critical ecosystem functions for many degraded drylands. However, climate change projections introduce large uncertainties about the sustainability of current reforestation practices. To cope with these uncertainties, adaptive restoration approaches are suggested, on the basis of improved plant quality, improved techniques for optimizing rain use efﬁciency in plantations, and exploring native plant species, including provenances and genotypes, for their resilience to ﬁre and water use efﬁciency.
The following values have no corresponding Zotero field: publisher: Springer Netherlands
Keywords: Mediterranean ecosystems; Nursery cultivation; Reforestation; Species selection; Water harvesting

Differential field response of two Mediterranean tree species to inputs of sewage sludge at the seedling stage - Valdecantos, Alejandro; Cortina, Jordi; Vallejo, V Ramón (Ecological Engineering, 2011)
Land degradation and desertiﬁcation is a common feature in Mediterranean landscapes due to extensive and intensive land use and natural orman induced disturbances. The ecosystemmay need external inputs to recover its composition and function as soils are often impoverished and vegetal key stone species lost. We evaluated the effects of the application of fresh and air-dried biosolids in the establishment and morphological and physiological performance of seedlings of Pinus halepensis and Quercus ilex under dry Mediterranean ﬁeld conditions. Seedling survival was not affected by biosolid treatments in any of the studied species both two and ten years after planting. During the ﬁrst two years, growth was enhanced by the two biosolid treatments in relation to control, although the change in the biomass allocation pattern differed between species. Rooting depthwas signiﬁcantly enhanced by liquid biosolid in Q. ilex and marginally reduced in P. halepensis as well as the exploration of soil. As a consequence, root-to-shoot ratio reduced signiﬁcantly with dry and liquid sludge due to promoted aboveground growth whilemaintaining and even reducing belowground fractions.An improvement ofthe nutritional status, offertilized seedlings especially of phosphorus, is the explanation for the better ﬁeld performance. Vector analysis revealed an important phosphorus limitation for both species that was overcome with the application of liquid (both species) and air-dried biosolid (pine). The higher growth of pine seedlings attained in the liquid biosolid treatment was coupled with a signiﬁcant decrease in foliar 13 C, suggesting lower water use efﬁciency. The signiﬁcant increase in foliar 15 N in the biosolid treatments in both species suggested that a large proportion of the total nitrogen uptake came from the applied biosolids. Instead, with regard to the low biosolid application rate used in the study, treatments had an overall positive effect as a restoration tool by improving nutritional status and promoting growth of planted seedlings.
Keywords: Biomass allocation pattern; Biosolids; Foliar isotopic composition; Pinus halepensis; Quercus ilex; Restoration; Vector diagnose

Prospective use of collected fog water in the restoration of degraded burned areas under dry Mediterranean conditions - Estrela, María J.; Valiente, José a.; Corell, David; Fuentes, David; Valdecantos, Alejandro (Agricultural and Forest Meteorology, 2009)
A mountainous plot located in the interior of the Valencia region (east coast of the Iberian Peninsula) was identiﬁed for reforestation using the fog-water collection potential prevailing in the area. Fog data were obtained by means of an instrument ensemble consisting of a passive cylindrical fog-water collector, a rain gauge, a wind direction and velocity sensor and a temperature and humidity probe. Preliminary results gave rise to the additional deployment of a low-cost 18-m2 ﬂat-panel collector connected to three 1000-l tanks for larger scale fog-water collection and storage. The 2007 annual rate of fog water that could be derived from the instrument ensemble amounted to 3.3 l/m2 /day, which turn out to ﬁll up the storage tanks completely in only 5 months, even though the ﬂat-panel collector could not be operative 100% of the time. The study made use of the in situ stored water and a micro-irrigation network to irrigate a plot of reforestation seedlings through small water pulses localized deep in the planting hole during the summer dry period. Until the present, this forest location had always shown a difﬁcult self-recovery due to the high level of land degradation resulting from recurrent forest ﬁres in the past. Results indicate that survival rates and seedling performance of the two species planted, Pinus pinaster and Quercus ilex, improved with the use of small timely waterings and additional treatments with composted biosolid.
Keywords: Micro-irrigation; passive fog collection; Reforestation; Valencia region

Prospective use of collected fog water in the restoration of degraded burned areas under dry Mediterranean conditions - Estrela, María J.; Valiente, José a; Corell, David; Fuentes, David; Valdecantos, Alejandro (Agricultural and Forest Meteorology, 2009)
A mountainous plot located in the interior of the Valencia region (east coast of the Iberian Peninsula) was identiﬁed for reforestation using the fog-water collection potential prevailing in the area. Fog data were obtained by means of an instrument ensemble consisting of a passive cylindrical fog-water collector, a rain gauge, a wind direction and velocity sensor and a temperature and humidity probe. Preliminary results gave rise to the additional deployment of a low-cost 18-m2 ﬂat-panel collector connected to three 1000-l tanks for larger scale fog-water collection and storage. The 2007 annual rate of fog water that could be derived from the instrument ensemble amounted to 3.3 l/m2 /day, which turn out to ﬁll up the storage tanks completely in only 5 months, even though the ﬂat-panel collector could not be operative 100% of the time. The study made use of the in situ stored water and a micro-irrigation network to irrigate a plot of reforestation seedlings through small water pulses localized deep in the planting hole during the summer dry period. Until the present, this forest location had always shown a difﬁcult self-recovery due to the high level of land degradation resulting from recurrent forest ﬁres in the past. Results indicate that survival rates and seedling performance of the two species planted, Pinus pinaster and Quercus ilex, improved with the use of small timely waterings and additional treatments with composted biosolid.
Keywords: Micro-irrigation; passive fog collection; Reforestation; Valencia region